Device-to-Device Communication in Wireless Network using mmWave within Small Cells and Exploiting Spatial Reuse - Harshad Kr, Dandage; Vilas S, Gaikwad (International Journal of Computer Sciences and Engineering, 2025)
Recently, extreme demand of mobile communication, small cells in millimeter wave bands within macro-cell network is attracting the attention in academics as well as the industries. Evolution of 4G is essential in keeping up with the exponential growth of mobile data network traffic. Up to 7GHz bandwidth has been allocated worldwide for license-free 60GHz radio frequency. Multiple giga-bites per second can be transmitted by utilizing the huge unlicensed bandwidth using mmWave communication in the 60GHz band. Numerous amount of spectrum available in micro frequencies are able to provide cost effective communication between the nodes in small cell via high capacity backhaul. Wireless backhaul is an attractive option for small cells as it provides a less expensive and easy-to-deploy over fiber. However, there are multitude of bands and features (e.g. LOS/NLOS, spatial multiplexing etc.) connected to wireless backhaul that need to be used smartly for small cells. Candidate bands include: sub-6 GHz band that is useful in non-line-of-sight (NLOS) scenarios, microwave band (6–42 GHz) that is used in point-to-point line-of-sight (LOS) scenarios, and mmWave bands (e.g. 60, 70 and 80 GHz) that are recently being commercially used in LOS scenarios. In many deployment topologies, it is more beneficial to use aggregator nodes, located at the roof tops of tall buildings near small cells. The protocol supports concurrent transmission in minimum frequency to the greater extent. Further to enhance the efficiency of network, performance analysis and different parameters will be calculated.